Self Help Groups a A Financial Model: Perceptions of Stakeholders (Global Journal of Management and Business Research, 2013)
In India, SHGs represent a unique approach to financial intermediation and innovation of credit delivery technique to enhance income generating activities. Sa-Dhan (2003) has sort out some of the unresolved issues in the context of quality assessment of SHGs. The main objective of this paper is to assess the opinion of the direct stakeholders (i.e. Promoters, Donors, Financial Institutions and the Group members) of SHGs regarding the issue whether SHG is a financial model. The study is conducted by using multi-stage random sampling method to collect primary data from the selected Development Blocks of Nagaon districts of Assam. From the ANOVA test on overall score of variables on financial model, it is concluded that all four groups’ means are not equal. It is observed that there exists enough evidence to conclude that there is significant association in the opinion of the direct stakeholders of SHGs regarding the issue whether SHG is a financial model. Further, it is observed that on thirteen (13) elements relating to financial model construct whose mean value is positive are considered as the key elements that recognise SHGs as the financial model of development.
Keywords: direct stakeholders; financial model; micro finance; perceptions of stakeholders; self help groups